(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article examines a didactic model for teaching mathematical analysis in a digital learning environment from both theoretical and practical perspectives. The integration of digital technologies, interactive methods, and assessment systems is considered a key factor in organizing the learning process. The content, methodological, technological, and assessment components of the didactic model are systematically analyzed. Furthermore, the implementation of the model in educational practice is shown to enhance students’ knowledge levels, analytical thinking skills, and independent learning abilities. The article also discusses the potential for improving the effectiveness of teaching mathematical analysis based on modern pedagogical approaches.